Selected English Novels and the Search for Sinhalese Identities - Fouad Abbas (Universitas Islam Tribakti Lirboyo Kediri, 2024)
The purpose of this study is to respond to the significant research conducted by several Sri Lankan English Novelists and Writers on the desire for identity. To defend and support the study project, extracts and opinions of notable English writers relevant to Sri Lankan literature are gathered from numerous primary and secondary sources. To establish a conclusion and defend the desired study effort on Sri Lankan English Novelists' demand for identity, a variety of international journals, books, magazines, and related material are investigated. The study examines the absence of a unified Sri Lankan identity in both English and Sinhala literary representations of the nation. While Sri Lanka's historical record may not support an inclusive national identity, one must wonder why literature, which is generally considered as a discourse that probes the unexpected and utopian, has failed to provide such an idealistic and inclusive vision of nationhood. The dominance of historical awareness in Sri Lankan (particularly Sinhala) cultural imagination, as well as the usage of realism as a mode of representation, produce a slew of challenges. The supremacy of the historical and realist genres must be seen as dialectically linked, with one strengthening the other: whereas history may serve to establish an authoritative stance for certain identities, realism can help to naturalize them. Sinhalese identity, Sinhalese in English Novels, and Sinhalese in Literature are some of the terms used to describe Sinhalese people.